Faktor Yang Mempengaruhi Cash Holding Perusahaan Sektor Barang Konsumsi Dan Aneka Industri - Felicia Rimu, Nurainun Bangun (Jurnal Paradigma Akuntansi, 2022)
The purpose of this research is to obtain empirical evidence about the effects of leverage, growth opportunity, and profitability on cash holding in companies in consumer goods industries & miscellaneous industrial sectors listed on the Indonesia Stock Exchange for the period of 2017-2019. This research used 40 samples of companies in consumer goods industries & miscellaneous industrial sectors that have been previously selected using purposive sampling method. Secondary data was used in the form of financial information from the financial statements. This research data was processed using EViews 10. The result of this research shows that profitability has a positive and significant effect on cash holding, while leverage and growth opportunity do not have a significant effect on cash holding. Suggestions for the next study is to add another independent variablesto be able to strengthen the ability of independent variables in explaining the dependent variable, such as cash flow, net working capital, and firm size.